Solvent exchange in a metal–organic framework single crystal monitored by dynamic in situ X‐ray diffraction. Issue 4 (1st August 2017) - Cox, Jordan M.; Walton, Ian M.; Bateman, Gage; Benson, Cassidy A.; Mitchell, Travis; Sylvester, Eric; Chen, Yu-Sheng; Benedict, Jason B.
Abstract : Dynamic in situ single crystal X‐ray diffraction revealed unique and important information about the structural reorganization that occurs upon guest exchange in a cobalt‐based metal organic framework. Abstract : Understanding the processes by which porous solid‐state materials adsorb and release guest molecules would represent a significant step towards developing rational design principles for functional porous materials. To elucidate the process of liquid exchange in these materials, dynamic in situ X‐ray diffraction techniques have been developed which utilize liquid‐phase chemical stimuli. Using these time‐resolved diffraction techniques, the ethanol solvation process in a flexible metal–organic framework [Co(AIP)(bpy)0.5 (H2 O)]·2H2 O was examined. The measurements provide important insight into the nature of the chemical transformation in this system including the presence of a previously unreported neat ethanol solvate structure.